Impact Evaluation of KPTS Policy in Pohuwato Regency - Harson Towalu (Pusat Publikasi Nusantara, 2023)
The implementation of the School Complete Achievement Card Policy (KPTS) has been going on for a decade or 10 (ten) years. The hope is to overcome the problem of students from poor families who cannot go to school for reasons of cost. For this reason, the purpose of this study is to describe the evaluation of the impact of KPTS Policy that has been going on for 10 (ten) years, in Pohuwato Regency. This study used descriptive methods, analysis and in-depth interviews. The results showed that the KPTS Policy had a positive impact on completing the education level of students from poor households, as well as making a significant contribution in reducing the dropout rate during the Covid-19 pandemic in Pohuwato Regency. This study also produced recommendations in the form of the need for policy innovation of local wisdom values with the Mopohulita model.